ISIS Communication Strategy - Styszyński, Marcin (Przegląd Strategiczny, 2016)
The present paper concerns studies on innovative communication and propaganda strategies of the main jihadist group called “the Islamic State of Iraq and Syria” (ISIS). In fact, media and Internet agitations enabled to reinforce ideological and operational influences of that organization and they affected different militants in the world who joined the battlefield in Syria and Iraq or carried out terrorist attacks in the West. Analysis of propaganda techniques reflects the following topics: liturgical speeches, official media channels, social medias and encrypted communication. Besides, the research demonstrates different audiences of ISIS communication strategy, which aims at affecting emotions and at stimulating opinions and reactions. The indoctrination concerns traditional, liturgical speeches delivered in Arabic by ISIS leader, Abu Bakr al-Baghdadi who targets local populations in mosques. Moreover, it also reflects new technologies such as radio and TV stations, official websites or social medias that include sophisticated programs, high quality pictures, graphics and videos. However, the paper also deals with some advanced computer and Internet technologies, which enable to protect identities of jihadists who follow important conversations about ISIS objectives.